The ICT Maintenance Evaluation In Mahkamah Konstitusi Republik Indonesia - Ivan Alexander (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
Mahkamah Konstitusi Republik Indonesia is an institution that has the authority to adjudicate constitutional examinations in Indonesia. In a government administration, every institution has the responsibility to manage its governance based on Information and Communication Technology (ICT). This work aims to evaluate the current maintenance flow in managing the video conference for the examination of petitioners, witnesses and remote experts. The evaluation result will be used to give recommendation to improve time, budget, and availability aspect of ICT Maintenance.